Pelatihan Pemanfaatan Media Panggung Boneka Bagi Guru Sekolah Minggu - Ireni Irnawati Pellokila; Maria Indriani Sesfao (Sekolah Tinggi Teologi Real Batam, 2021)
The purpose of this activity is to provide understanding and knowledge to Sunday school teachers about learning media as well as an experience for Sunday school teachers in the Central Kupang City class about the importance of using learning media and school activities and the use of puppet stage media. This activity is intended to add insight and skills Sunday school teachers in utilizing various available media in delivering interesting Bible stories to children, so that the process of Sunday school activities can run with enthusiasm and joy. Because in school learning that is carried out in the congregation is still very boring for children, especially for small and middle class children, the same teaching methods are carried out from week to week by Sunday school teachers such as stories and coloring pictures. This causes Sunday school children to feel lazy to come to Sunday school, let alone listen to the stories that are told. Because especially for children's classes, they prefer to listen to something interesting. The methods used in this service activity are socialization, mentoring and training, and reflection. From the service activities carried out, the results obtained are Sunday school teachers understand about learning media and the importance of using learning media in Sunday schools to attract children's interest in participating in Sunday school activities, especially using the puppet stage media which is interesting and fun, even school teachers are starting to can use and have the initiative to make their own existing learning media, especially dolls from patchwork/recycled materials. Keywords: Sunday school; media; puppet stage; training AbstrakTujuan dari kegiatan ini adalah memberikan pemahaman dan pengetahuan kepada guru sekolah minggu tentang media pembelajaran serta sebagai pengalaman bagi guru sekolah minggu di klasis Kota Kupang Tengah tentang pentingnya pemanfaatan media pembelajaran dan kegiatan sekolah dan penggunaan media panggung boneka, Kegiatan ini dimaksudkan untuk menambah wawasan dan keterampilan guru sekolah minggu dalam pemanfaatan berbagai media yang tersedia dalam penyampaian cerita Alkitab kepada anak yang menarik, sehingga proses kegiatan sekolah minggu dapat berjalan dengan semangat dan sukacita. Karena dalam pembelajaran sekolah yang dilakukan di jemaat masih sangat membosankan bagi anak, khususnya anak kelas kecil dan kelas tanggung, metode mengajar yang sama yang dilakuakn dari minggu ke minggu oleh pengajar sekolah minggu seperti cerita dan mewarnai gambar. Hal ini menyebabkan anak sekolah minggu merasa malas untuk datang ke sekolah minggu, apalagi mendegarkan cerita yang disampaikan. Sebab khusus untuk kelas anak, lebih senang mendegarkan sesuatu yang menarik. Metode yang digunakan dalam kegiatan pengabdian ini adalah sosialisasi, pendampingan dan pelatihan, serta refleksi. Dari kegiatan pengabdian yang dilakukan, maka hasil yang diperoleh yaitu guru sekolah minggu memahami tentang media pembelajaran dan pentingnya pemanfaatan media pembelajaran di sekolah minggu untuk menarik minat anak dalam mengikuti kegiatan sekolah minggu, khususnya menggunakan media panggung boneka yang menarik dan menyenangkan, bahkan guru sekolah mulai dapat menggunakan dan memiiki inisiatif untuk membuat sendiri media belajar yang ada khususnya boneka dari bahan perca/daur ulang. Kata kunci: sekolah minggu; media; panggung boneka; pelatihan